Workplace violence among dental surgeons - A survey - Reshma Poothakulath Krishnan; Pratibha Ramani; Gheena Sukumaran; Abilasha Ramasubramanian; Monica Karunagaran; R Hannah (Wolters Kluwer Medknow Publications, 2021)
Background: Workplace violence is a multi-causal, multifaceted, public health, legal and social problem faced by all occupations worldwide. Recently, there has been an increase in the prevalence of workplace violence against doctors. Even though the government has attempted to address these problems in India, doctors are still experiencing violence in their workplaces. Aim: The aim of this survey was to determine the prevalence and awareness of workplace violence among dental surgeons. Methodology: This cross-sectional study was conducted among the dental surgeons. A self-administered questionnaire containing 15 questions was made and validated. A Web-based questionnaire was developed using Google forms and was circulated. A total of 112 responses were obtained. Questions were answered with "yes" "no" or by marking the correct responses. Frequency analysis and percentage analysis were done with the obtained results. Results: Our study showed that 74.1% of the participants heard about the workplace violence and 30.4% faced violence in their clinic. The nature of the violence was physical in 0.9%, verbal in 39.3%, and sexual in 0.9% among the participants who faced violence. A total of 92.9% of the participants reported that they require policies and guidelines against this workplace violence. Conclusion: Dental surgeons should have proper knowledge about the work-related violence and methods to control this violence. Policies, procedures, and intervention strategies should be undertaken to manage this alarming issues.